Investigation of role of Rab GTPases in fruit ripening in tomato (Solanum lycopersicum L.) - Saini, Kunal (2018)
Tomato (Solanum lycopersicum L.) is one of the most important vegetable crops cultivated worldwide. Rab GTPases are involved in the processes of intracellular membrane traffic, protein secretion and signal responses for targeting of molecules for secretion into the cell wall. Silencing these genes is likely to affect fruit softening by blocking the export of a range of cell wall modifying factors. A cDNA clone from the tomato fruit encoding a protein homologous to rab11/YPT3 was developmentally regulated during fruit ripening. Antisense fruit changed colour but failed to soften normally (Lu et al., 2001). The aim of the project is to investigate the role of Rabs and other elements of intracellular membrane trafficking in secretion of cell wall modifying factors associated with fruit softening. Sixty genes encoding Rab GTPases in tomato were identified by in silico analysis by screening the EST databases and were classified as Rab GTPases according to Release 12 of TIGR Tomato Gene Index. The genes were grouped into 8 different functional classes ranging from Rab1, 2, 5, 6, 7, 8, 11 and Rab18. A phyletic tree was constructed which indicated all the genes were falling into 8 different clades belonging to each class. A comprehensive in silico analysis of other genes involved in intracellular membrane trafficking like Rab GEF, GAP, GDI, and other genes like ARF, ARL, RAN, ROP, SAR (Vernoud et al., 2003)was done by using the same databases. The results showed that there are thirteen ARF GTPases, eighteen ARL GTPases, seven SAR GTPases, eight ROP GTPases, and a total of nine RAN GTPases in tomato. The Rab GTPase interacting partners like GAP, GDI and GEF were also identified. The results revealed that there are twenty three Rab GAPs, two Rab GEFs and a total of six Rab GDIs were found. The information about the genes was updated throughout the course of the present investigation right from the TIGR DFCI TGI release11,12 and 13, SGN Unigene Build 1 and 2 as well the latest release of tomato whole genome sequence database at SGN from SGN ITAG-1 to ITAG-2.4. After the final analysis, a total of 55 Rab GTPases were grouped into eight different sub classes with five Rab1/D, five Rab2/B, four Rab5/F, three Rab6/H, four Rab7/G, five Rab8/E, twenty five Rab11/A and four Rab18/C. Solyc Rab11/A was further classified into 6 sub groups from A1 to A6. The results of classification led to identification of seven RabA1, six RabA2, one RabA3, five RabA4, five RabA5 and one RabA6. The phylogenetic analysis of the tomato Rab GTPases and a comparative analysis with Arabidopsis Rab GTPase confirmed the groups and classes. Similarly four RAN, ten ROP, twelve ARF, four SAR, six ARL GTPases were identified. In case of ARF GTPases seven ARFA, four ARFB, and one ARF C was found. The regulators of small GTPases identified in tomato had one RAB GEF, two ROP GEF, four RABGDI and five ROP GDI, twenty two RabGAP, 2 RAN GAP, nine ROP GAP and nineteen ARF GAP. Comparative phyletic analysis of all the above with Arabidopsis genes confirmed the classification.